Estudios y Diseño estructural del Pavimento del Barrio Urseza 2 Sector 1 del cantón Machala, provincia de El Oro - Cabrera Jiménez, Edwin José (2015)
The route under consideration , which is in poor condition has caused discomfort and difficulties for the residents of this neighborhood , making difficult the normal vehicular and pedestrian transport. For this reason this project aims , the study of the way that best meets the geometric and structural characteristics according to the rules of M.T.O.P. to ensure that the inhabitants of these sites , a functional way , safe, economical and aesthetics.